Profiling of the Causative Bacteria in Infected Lymphocysts after Lymphadenectomy for Gynecologic Cancer by Pyrosequencing the 16S Ribosomal RNA Gene Using Next-Generation Sequencing Technology - Yuya Nogami; Kouji Banno; Masataka Adachi; Haruko Kunitomi; Yusuke Kobayashi; Eiichiro Tominaga; Daisuke Aoki (Hindawi Limited, 2019)
Background. Surgery for gynecologic cancer with lymphadenectomy and pelvic radiotherapy can produce lymphoceles that sometimes complicate with infection, resulting in abscesses. The true pathogenic bacteria of abscesses are not always found because of false-negative results due to administered antibiotics and difficulty with detection, including for anaerobic bacteria. Analyzing bacteria flora by next-generation sequencing (NGS) using 16S ribosomal DNA may reveal the true pathogenic bacteria in abscesses. This is the first report on causative pathogens for infectious lymphocele using this technology. Methods. The subjects were patients who developed infectious lymphocele after surgery for gynecologic cancer at our hospital from July 2015 to September 2016. NGS analyses of bacterial flora were performed using specimens preserved at -80°C. Two steps of PCR were performed for purified DNA samples to obtain sequence libraries. Processing of sequence data, including operational taxonomic unit (OTU) definition, taxonomy assignment, and an OTU BLAST search were performed. All patients gave written informed consent and the study was approved by the institutional research ethics committee. Results. Six patients underwent puncture and drainage. The result in most cases indicated a single causative pathogen, including Staphylococcus lugdunensis, Streptococcus dysgalactiae, Streptococcus equinus, Enterococcus saccharolyticus, and Escherichia coli. Conclusions. NGS revealed that the causative bacteria in lymphocele infection are normally a single strain, such as a surface Gram-positive coccus or enteric bacteria. Antibiotics should be chosen as appropriate for elimination of these respective bacteria.